(untitled) (REVISTA NODO, 2026)
Throughout human history, taboos and prejudices have existed, along with scientific attacks against transgender and transvestite people. Today, this important discussion continues, aiming to raise awareness and demand their human rights. In this work, I will share some reflections on the photographic work of Susana Casarin, who has brought visibility to transgender people in her series Realities and Desires (2012), Muxes and Apsaras (2020), which have been exhibited in national and international museums. Furthermore, one of her series, Muxes, inspired a very interesting short documentary by screenwriter and director Javier Solórzano Casarin. Photography, as an art discipline, has played a relevant role in this sense and is a support for showing these people in their essence.